The importance of interdisciplinary work during undergraduate nursing studies - Guimarães, Fernanda Pereira; Barcelos, Karine Luciano; Carvalho, Carla Aparecida de; Lieberenz, Larissa Viana Almeida de; Resende, Fernanda Amaral; Pires, Edina da Conceição Rodrigues (Seven Editora, 2023)
Undergraduate nursing courses are seeking, through interdisciplinary work, the training of professionals capable of promoting the integral health of human beings. This process of (re)construction of knowledge places the student at the center of the teaching-learning process. Thus, the objective of this study was to evaluate the perception of nurses in relation to the interdisciplinary work carried out in undergraduate courses, as academics and, today, as professionals. We opted for a descriptive field research, carried out with a questionnaire, applied through the Facebook social network of the Meta® group to 96 nurses who performed interdisciplinary work throughout their undergraduate studies. The result of the research showed that there was a change in the interviewees' perception of the importance of work during the course and after graduation. Of those surveyed, 70% said they did not consider work important at the beginning of the course, while 88% said they understood the importance of it after graduation. Exactly 76% of the nurses interviewed considered interdisciplinary work more difficult than other jobs and 59% claimed that they would not have done the work if it had not been a curricular requirement. Despite the complexity, the curricular requirement enabled the students to have the interdisciplinary experience necessary for professional life, since 83% of the interviewees recognized the importance of the work for the profession. Thus, the interdisciplinary work applied during undergraduate nursing, despite the challenges, changed the perspective of nurses in relation to knowledge, making them critical, reflective professionals, capable of working as a team, promoting integral health and exercising citizenship. DOI:https://doi.org/10.56238/sevened2023.008-001